Emergence of norovirus GII.P16-GII.2 strains in patients with acute gastroenteritis in Huzhou, China, 2016–2017 - Jiankang Han; Xiaofang Wu; Liping Chen; Yun Fu; Deshun Xu; Peng Zhang; Lei Ji (BMC Infectious Diseases, 2018)
Abstract Background In late 2016, an uncommon recombinant NoV genotype called GII.P16-GII.2 caused a sharp increase in outbreaks of acute gastroenteritis in different countries of Asia and Europe, including China. However, we did not observe a drastic increase in sporadic norovirus cases in the winter of 2016 in Huzhou. Therefore, we investigate the prevalence and genetic diversity of NoVs in the sporadic acute gastroenteritis (AGE) cases from January 2016 to December 2017 in Huzhou City, Zhejiang, China. Methods From January 2016 to December 2017, a total of 1001 specimens collected from patients with AGE were screened for NoV by real-time RT-PCR. Partial sequences of the RNA-dependent RNA polymerase (RdRp) and capsid gene of the positive samples were amplified by RT-PCR and sequenced. Genotypes of NoV were confirmed by online NoV typing tool and phylogenetic analysis. Complete VP1 sequences of GII.P16-GII.2 strains detected in this study were further obtained and subjected into sequence analysis. Results In total, 204 (20.4%) specimens were identified as NoV-positive. GII genogroup accounted for most of the NoV-infected cases (98.0%, 200/204). NoV infection was found in all age groups tested (< 5, 5–15, 16–20, 21–30, 31–40, 41–50, 51–60, and >60 years), with the 5–15 year age group having the highest detection rate (17/49, 34.7%). Higher activity of NoV infection could be seen in winter-spring season. The predominant NoV genotypes have changed from GII.Pe-GII.4 Sydney2012 and GII.P17-GII.17 in 2016 to GII.P16-GII.2, GII.Pe-GII.4 Sydney2012 and GII.P17-GII.17 in 2017. Phylogenetic analyses revealed that 2016–2017 GII.P16-GII.2 strains were most closely related to Japan 2010–2012 cluster in VP1 region and no common mutations were found in the amino acids of the HBGA-binding sites and the predicted epitopes. Conclusions We report the emergence of GII.P16-GII.2 strains and characterize the molecular epidemiological patterns NoV infection between January 2016 and December 2017 in Huzhou. The predominant genotypes of NoV during our study period are diverse. VP1 amino acid sequences of 2016–2017 GII.P16-GII.2 strains remain static after one year of circulation.